2016
DOI: 10.5194/angeo-34-529-2016
|View full text |Cite
|
Sign up to set email alerts
|

A multi-platform investigation of midlatitude sporadic <i>E</i> and its ties to <i>E</i>–<i>F</i> coupling and meteor activity

Abstract: Abstract. This paper describes the results of a multiplatform observing campaign aimed at studying midlatitude sporadic E (E s ) and associated ionospheric phenomena. The assets used were the digisonde in Boulder, Colorado; the first station of the Long Wavelength Array, LWA1, in New Mexico; the transmitters of the radio station WWV in Colorado; and 61 continuously operating GPS receivers between LWA1 and WWV. The results show that southwestward-directed medium-scale traveling ionospheric disturbances (MSTIDs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Because the video carrier is only amplitude modulated, it is extremely spectrally narrow ( 35 Hz wide) and thus these Doppler measurements require no demodulation. Helmboldt () also showed that an arc of backscattering sources is often seen to the north within 55.25‐MHz observations that is consistent with coherent backscatter from field‐aligned irregularities within the E region, presumably associated with Es.…”
Section: Data Collection and Analysismentioning
confidence: 72%
See 1 more Smart Citation
“…Because the video carrier is only amplitude modulated, it is extremely spectrally narrow ( 35 Hz wide) and thus these Doppler measurements require no demodulation. Helmboldt () also showed that an arc of backscattering sources is often seen to the north within 55.25‐MHz observations that is consistent with coherent backscatter from field‐aligned irregularities within the E region, presumably associated with Es.…”
Section: Data Collection and Analysismentioning
confidence: 72%
“…This is reasonably consistent with the properties of dense Es clouds observed by several other authors, often in association with so‐called quasiperiodic echoes (e.g., Bernhardt, ; Bowman, ; Pan & Tsunoda, ; Hysell et al, ; Hysell & Burcham, ; Larsen, ). In fact, using a different set of LWA1 observations in combination with data from the Boulder, Colorado, Digisonde, Helmboldt () found that the northern arc of sources associated with Es FAIs appeared most prominently when Es layers with large peak densities (foEs 4 MHz) were present.…”
Section: Resultsmentioning
confidence: 99%
“…near local midnight, i.e., 15 UT and 07 UT in Korea and Idaho, respectively. There is significant evidence that disturbances driven by polarization electric fields are more prevalent when FoEs is lower (J. F. Helmboldt, 2012;J. Helmboldt, 2016).…”
Section: Observations 21 Instrumentation and Methodsmentioning
confidence: 99%
“…Also in both cases, the peak E S electron density as traced by FoEs was lower (2.5 MHz) near local midnight, that is, 15 and 07 UT in Korea and Idaho, respectively. There is significant evidence that disturbances driven by polarization electric fields are more prevalent when FoEs is lower (Helmboldt, 2012, 2016). Both the ap and F 10.7 indices were relatively low, as expected near solar minimum.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation